Comparison between left and right radial access for coronary angiography - AC, Cázares-Díazleal; J, Dorantes-García; R, Kiamco-Castillo; G, Payro-Ramirez; J, Betuel-Ivey; E, Lozano-Sabido; J, Arce-González (Journal of Cardiovascular Medicine and Cardiology, 2020)
In the 1980s, Campeu and Kiemeneij introduced the radial approach for angiography and angioplasty, respectively, in 2017 Kiemeneij described the site of radial distal access to the snuffbox, as the viability and safety of the left approach, either conventional or distal, remains a concern and there are no studies evaluating comfort yet. We randomly assigned 55 patients (9 were excluded), to either left radial access or right radial access (27 pts vs 28 pts). The primary end point was patient´s comfort, contrast volume, distance between first operator and patient, number of angiography catheters, fluoroscopy time. As secondary safety endpoints we include radial spasm and procedure related bleeding. Statistical analysis was done with descriptive statistics, T student for quantitative variables and square chi for qualitative variables. From January 2019 to September 2019 we enrolled 64 patients, (9 were excluded) Stable coronary artery disease was the most common indication for angiography (60% left vs 43% right). Both access were perceived as comfortable (4.29 left vs 4.18 right P=0.549), the amount of contrast volume used was (103 + 85 ml vs 88+55 ml P=0.436, distance between intensifier-researcher (47.6 cm +4.6 right vs 47.7cms +4.8 left, p = 0.941). In safety endpoints the presence of bleeding was 7% vs 7% (P=0.99) and radial artery spasm 26% and 11% respectively (P=0.177). In terms of comfort and safety there is no difference between left and right radial access, both access sites can be done with femoral and radial dedicated catheters in stable coronary disease and acute coronary syndrome coronary.